The efficiency of porkers production of intensively and extensively feeded - Pepliński , Benedykt; Wajszczuk, Karol; Baum, Rafał; Majchrzycki, Dariusz; Wawrzynowicz, Jacek; Lisiak, Dariusz; Janiszewski, Piotr (Applied Studies in Agribusiness and Commerce, 2013)
The aim of this study is a comparative analysis of the costs of production of intensively and extensively fed porkers in view of the qualitative parameters of meat obtained after slaughter. The production experiment, which involved the parallel fattening of 3 groups of 30 porkers (fed intensively up to a weight of about 120 kg and extensively up to weights of about 100 kg and 120 kg), was carried out between 2011 and 2012 in a deliberately selected farm. The researchers assumed average prices of the means of production and prices of livestock pigs in individual meatiness classes noted in Poland in 2012. The fattening started when the animals weighed about 40 kg. The feeds used for extensive fattening contained less total protein, energy and basic exogenous amino acids, but more raw fibre. The analysis proved that the extensive production of porkers up to 100 kg in 2012 was not profitable. The most profitable production was the intensive production up to 120 kg (a profit of €0.100 per kg, whereas in the extensive feeding up to 120 kg the profit was €0.072 per kg. The porkers which were fed less intensively had a higher slaughter value, thinner fatback, higher dressing percentage and smaller content of fatback in the half-carcase, whereas their meat contained more water and less protein, fat and ash than the meat from the group of porkers fed with the mix richer in protein and energy.